Obesity alters cortical and trabecular bone density and geometry in women - Sukumar, D. (2010)
SUMMARY: The goal in this study was to determine the relationship between body mass index and trabecular and cortical bone using quantitative computed tomography. A higher body mass index (BMI) was positively associated with trabecular and cortical bone parameters, and serum parathyroid hormone, and negatively associated with cortical volumetric bone mineral density (vBMD) and serum 25-hydroxy-vitamin D. When BMI is greater than 35 kg/m(2), adiposity affects vBMD and may explain the higher fracture risk in this population without low BMD. INTRODUCTION: The influence of adult obesity on the trabecular and cortical bone, geometry, and strength has not been fully addressed. The goal in this study was to determine the relationship between body mass index and trabecular and cortical bone mass and geometry, over a wide range of body weights. METHODS: We examined 211 women (25–71 years; BMI 18–57 kg/m(2)) who were classified into three categories of BMI (kg/m(2)) including normal-weight (BMI<25), overweight and obese-class I (BMI 25–35) and obese-class II–III (BMI>35), and also by menopausal status. Volumetric bone mineral density (mg/cm(3)), trabecular, and cortical components as well as geometric characteristics at the 4%, 38%, and 66% from the distal tibia were measured by peripheral quantitative computed tomography, and serum was analyzed for parathyroid hormone (PTH) and 25-hydroxy-vitamin D (25OHD). RESULTS: Higher BMI was associated with greater values of trabecular bone and cortical BMC and area and PTH (r>0.39, p<0.001), but lower cortical vBMD and 25OHD (r>−0.27, p<0.001). When controlling for lower leg muscle area, fat area was inversely associated with cortical vBMD (r=−0.16, p<0.05). Premenopausal obese women with both higher BMI and PTH had lower cortical vBMD (r<−0.40, p<0.001). While age is a predictor for most bone variables, fat mass explains more variance for vBMD, and lean mass and 25OHD explain greater variance in geometric and strength indices (p<0.05). CONCLUSIONS: Severe obesity (BMI>35) increases trabecular vBMD and in the presence of a higher PTH is associated with a lower cortical vBMD without compromising bone geometry and strength. Whether or not a lower cortical vBMD in obesity influences fracture risk over time needs to be further explored.